Analisis Membran Filter Mikron Terhadap Produktivitas Reverse Osmosis Fresh Water Maker di MT. SC Warrior - Luvis Figo; Ali Khamdilah; Eko Nur Hidayat; Fajar Pujiyanto (Politeknik Bumi Akpelni Semarang, 2025)
MT. SC Warrior ship is a tanker designed to transport processed oil cargo on long-distance shipping routes. One of the main facilities to support ship shipping activities is the Reverse Osmosis (RO) Fresh Water Maker system. This equipment functions to produce fresh water with the main ingredient being sea water. The RO system utilizes a high pressure pump and a micron filter membrane as the main components in the process of converting seawater into fresh water. The problem with RO is a decrease in fresh water productivity, causing a fresh water deficit in the ship. The problem is caused by low hydrostatic pressure in the RO system, and the micron filter membrane's function is not optimal in filtering sea water. This condition disrupts ship operations where the availability of fresh water is insufficient in quantity. In order to avoid the same problems, proper preventive and corrective measures are needed. Planned maintenance according to PMS and correct procedures must be carried out properly and correctly, which is important in maintaining the performance of the RO system. The need for consistent and proper maintenance, it is hoped that the RO system can continue to function effectively to support ship operations without obstacles.